2014
DOI: 10.1016/j.ijsu.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors for tissue healing deficit and leakage in geriatric critically ill patients receiving emergent abdominal surgery: A case control study

Abstract: Persistent post operative vasopressor use and hypoalbuminemia are associated with higher rate of morbidity and mortality after emergent abdominal surgery in geriatric critically ill patients. Early recognition is essential for proper management. Further studies are required for a better understanding in identifying risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Hypoalbuminemia has been shown to be a negative prognostic factor for surgical 35 and nonsurgical patients, 36 and predictor of 30-day postoperative morbidity and mortality. 31,37 Nevertheless, Wu et al 38 showed that albumin administration did not improve the rate of reoperation and serious surgical complications, a finding that suggests that hypoalbuminemia is a surrogate for a broader poor metabolic state.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia has been shown to be a negative prognostic factor for surgical 35 and nonsurgical patients, 36 and predictor of 30-day postoperative morbidity and mortality. 31,37 Nevertheless, Wu et al 38 showed that albumin administration did not improve the rate of reoperation and serious surgical complications, a finding that suggests that hypoalbuminemia is a surrogate for a broader poor metabolic state.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that physiological concentrations of albumin selectively inhibit TNF-α-induced upregulation of VCAM-1 expression and monocyte adhesion, most likely by inhibiting NF-κB activation in a GSH-independent manner, thereby acting as an anti-inflammatory agent toward endothelial cells. 13 There is increasing evidence that hypoproteinemia is closely related to wound healing because it contributes to reduced collagen formation and wound dehiscence and results in poor wound-healing rates after abdominal 14 and lumbar surgeries 15 and in perineal wound healing. 16,17 Recent studies of patients with a DFU showed that serum albumin level was significantly lower than that in diabetic patients without a DFU 18 and that low albumin level was an independent predictor for delayed wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that hypoproteinemia is closely related to wound healing because it contributes to reduced collagen formation and wound dehiscence and results in poor wound-healing rates after abdominal14 and lumbar surgeries15 and in perineal wound healing 16,17. Recent studies of patients with a DFU showed that serum albumin level was significantly lower than that in diabetic patients without a DFU18 and that low albumin level was an independent predictor for delayed wound healing 19.…”
Section: Introductionmentioning
confidence: 99%